The Influence of Instagram on Medical Education in the age of Artificial Intelligence: A formal assessment of its utility in Health Education: The Influence of Instagram on Medical Education in the age of Artificial Intelligence: A formal assessment of its utility in Health Education - Araujo-Filho, Irami; Meneses do Rêgo, Amália Cinthia (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2024)
This review article explores the intricate role of Instagram and artificial intelligence (AI) in medical education and health promotion. It scrutinizes the dual-edged nature of these technologies, highlighting their potential benefits in disseminating health information and the challenges they present, particularly regarding information accuracy and misinformation. The analysis underscores Instagram's unique capacity to reach broad audiences with visually engaging health education content, emphasizing its utility in public health campaigns and crisis communication. However, the platform's susceptibility to spreading inaccurate health information necessitates urgent and proactive strategies for mitigation. Integrating AI in content management and moderation on Instagram is a promising solution to address misinformation, with the effectiveness of such technologies hinging on continuous research, development, and ethical implementation. The review advocates for developing evidence-based content and engagement strategies by health professionals and educators to maximize benefits and minimize risks associated with Instagram use. It concludes that a collaborative, multidisciplinary approach involving health professionals, educators, researchers, technology developers, and regulators is essential to leverage Instagram and AI for global health improvement responsibly.